1998
DOI: 10.1128/jb.180.11.2883-2888.1998
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional Modifications in 16S and 23S rRNAs of the Archaeal Hyperthermophile Sulfolobus solfataricus

Abstract: Posttranscriptional modification is common to many types of RNA, but the majority of information concerning structure and function of modification is derived principally from tRNA. By contrast, less is known about modification in rRNA in spite of accumulating evidence for its direct participation in translation. The structural identities and approximate molar levels of modifications have been established for 16S and 23S rRNAs of the archaeal hyperthermophile Sulfolobus solfactaricus by using combined chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(58 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…In this paper we report the mapping of 8 residues in the LSU rRNA of a hyperthermophile Archaea, Sulfolobus acidocaldarius. Six 8 residues were detected in the studied rRNA regions, which is slightly higher than the 3.7 þ 0.1 mol/mol of 8 residues detected by chromatography/mass spectrometry in the S. sulfolobus LSU rRNA [40] and the four 8 residues localised in the H. halobium LSU rRNA. Only a few modi¢cation positions are conserved between Bacteria and Archaea, while the others seem to be speci¢c for Archaea or common to Archaea and Eucarya.…”
Section: Introductionmentioning
confidence: 55%
“…In this paper we report the mapping of 8 residues in the LSU rRNA of a hyperthermophile Archaea, Sulfolobus acidocaldarius. Six 8 residues were detected in the studied rRNA regions, which is slightly higher than the 3.7 þ 0.1 mol/mol of 8 residues detected by chromatography/mass spectrometry in the S. sulfolobus LSU rRNA [40] and the four 8 residues localised in the H. halobium LSU rRNA. Only a few modi¢cation positions are conserved between Bacteria and Archaea, while the others seem to be speci¢c for Archaea or common to Archaea and Eucarya.…”
Section: Introductionmentioning
confidence: 55%
“…Our observations raise the issue of whether Sso7d exhibits any speci¢city in vivo. Although we do not have any de¢nite answer at present, it should be pointed out that RNAs from S. solfataricus have been reported to have exceptionally high modi¢cation levels: for instance, in both 16S and 23S rRNAs several residues are methylated at O-2P of ribose, a modi¢ca- tion that enhances the stability of the polynucleotide chain at high temperatures [31]. These modi¢cations may therefore lead to a more restricted in vivo speci¢city of Sso7d.…”
Section: Discussionmentioning
confidence: 77%
“…Archaeal rRNAs are rich in post-transcriptionally modified nucleotides. Examination of the extent of rRNA modifications in the hyperthermophilic archaeon Sulfolobus solfataricus revealed an exceptionally high proportion of modifications as compared to prokaryotic organisms, with 38 modified sites in the 16S rRNA and 50 in the 23S rRNA for the archaeon, compared with 11 and 23 sites, respectively, in Escherichia coli [33]. The principal modifications in S. solfataricus 16S and 23S rRNAs are methylation of the 2'-OH group of sugar residues (2'-O-methylation).…”
Section: Given What Is Known Today About Ribozymes Does It Tell Us Amentioning
confidence: 99%
“…The principal modifications in S. solfataricus 16S and 23S rRNAs are methylation of the 2'-OH group of sugar residues (2'-O-methylation). It has been suggested that the 2'-O-Me groups act to stabilize RNA stems by maintaining the sugar residues in the more rigid C(3')-endo-conformation [33]. Moreover, an increase in ribose methylation was observed in rRNAs of S. solfataricus (21 -24% increase) with progressive temperature increase of the culture [33].…”
Section: Given What Is Known Today About Ribozymes Does It Tell Us Amentioning
confidence: 99%
See 1 more Smart Citation